Audiologic and Otologic Clinical Manifestations of Loeys‐Dietz Syndrome: A Heritable Connective Tissue Disorder. (11th May 2021) - Jeon, Jun W.; Christensen, Julie; Chisholm, Jennifer; Zalewski, Christopher; Rasooly, Marjohn; Dempsey, Caeden; Magnani, Alaina; Frischmeyer‐Guerrerio, Pamela; Brewer, Carmen C.; Kim, Hung Jeffrey
Abstract : Objective: Loeys‐Dietz syndrome (LDS) is a rare genetic connective tissue disorder resulting from TGF‐ß signaling pathway defects and characterized by a wide spectrum of aortic aneurysm, arterial tortuosity, and various extravascular abnormalities. This study describes the audiologic, otologic, and craniofacial manifestations of LDS. Study Design: Consecutive cross‐sectional study. Setting: Tertiary medical research institute. Methods: Audiologic and clinical evaluations were conducted among 36 patients (mean ± SD age, 24 ± 17 years; 54% female) with genetically confirmed LDS. Cases were categorized into genetically based LDS types 1 to 4 ( TGFBR1, TGFBR2, SMAD3, TGFB2, respectively). Audiometric characteristics included degree and type of hearing loss: subclinical, conductive, mixed, and sensorineural. Results: LDS types 1 to 4 included 11, 13, 5, and 7 patients, respectively. In LDS‐1, 27% had bilateral conductive hearing loss; 9%, unilateral mixed; and 36%, subclinical. In LDS‐2, 38% had conductive hearing loss and 38% subclinical. In LDS‐3 and LDS‐4, 40% and 43% had bilateral sensorineural hearing loss, respectively. Degree of hearing loss ranged from mild to moderate. Bifid uvula was observed only in LDS‐1 (55%) and LDS‐2 (62%). Submucosal/hard cleft palates were primarily in LDS‐1 and LDS‐2. Posttympanostomy tympanic membrane perforations occurred in 45% (10/22 ears) of LDS‐1 and LDS‐2. There were 4 cases of cholesteatoma: 3 middle ear (LDS‐1 and LDS‐2) and 1 external ear canal (LDS‐3). Conclusion: Conductive hearing loss, bifid uvula/cleft palate, and posttympanostomy tympanic membrane perforation are more common in LDS‐1 and LDS‐2 than LDS‐3 and LDS‐4, while sensorineural hearing loss was present only in LDS‐3 and LDS‐4. These LDS‐associated key clinical presentations may facilitate an early diagnosis of LDS and thus prompt intervention to prevent related detrimental outcomes.